Konsep Kesetaraan dalam Kesaksian Perempuan: Antara Perspektif Wahyu dan Perspektif Gender - Henri Shalahuddin (Universitas Darussalam Gontor, 2016)
The following article tries to research the concept of equality in women’s testimony, either in revelation perspective or gender one. For feminists, women’s testimony in Islam which is considered half of the man’s testimony has been led to discrimination against women in the public sector. In Islam, implementing testimony is farḍu kifâyah, including the testimony implemented by women. A woman’s testimony is accepted in all cases that may not be done by men absolutely. Related to this, there are fundamental differences on the issue of women’s testimony between viewpoints based on gender and viewpoints based on Islamic thought. Gender issues in the perspective of Islamic thought are basically always in harmony with nature and the human mind at all times and places. Thus, it is surprising if a Muslim believes that in Islamic law there are aspects of injustice and discrimination against women, he tries to deconstruct interpretation of the Qur’an and the hadits as the feminists do. The principle of fairness and equality in Islam is not just restricted to the meaning of the empirical and material. But it also contains elements of spiritual, welfare, a guarantee of rights and obligations, the aspect of helping each other, supporting each other, and being responsible. Islam does not interpret men and women as a separate entity, apart, and competing. The difference in the rights, obligations and rukhṣah in the law, can not be interpreted as preferential treatment or discrimination.